Impact of the Agricultural Sector on Output, GDRP and Workforce Compensation - Eddy Silamat; Priyono Priyono; Hernawati Hernawati (International Journal of Economics, Business and Innovation Research, 2023)
The agricultural sector plays a strategic role in the structure of the Indonesian economy. The agricultural sector policy will be optimal if it considers subsectors that have high multipliers. An increase in final demand in the sub-sector will increase the output of the sub-sector itself and other sub-sectors in the economy. The objective of this study was to calculate the contribution of the agricultural sector in the structure of the national economy, calculate the value of the multiplier effect and the relation of the agricultural sector to other sectors, and analyzing the impact of the agriculture, livestock, forestry and fisheries sectors on output, gross domestic regional product (GDRP), and workforce compensation. Secondary data were obtained from the Input-Output 2010 table released by BPS in December 2015 and Input-Output table updating by BEKRAF in December 2017. Results showed that the agriculture, livestock, forestry, and fisheries were still the mainstay after the processing industry with a contribution accounted by 13.28%. The plantation crops sub-sector has the forward linkages highest with a multiplier effect accounted by 3.1251. The sub-sectors which have the highest direct backward linkages were the livestock sub-sector with multiplier effect accounted by 1.6185. The plantation crops sub-sector has the highest contribution to the output, GDRP, and workforce compensation for agriculture, livestock, forestry, and fisheries. Household consumption was the most dominant contributor and LNPRT consumption was the minimum contributor for output, GDRP, and workforce compensation.